2017
DOI: 10.1152/ajpgi.00437.2016
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intravenous corticotropin-releasing hormone administration on esophageal sensitivity and motility in health

Abstract: Esophageal hypersensitivity is important in gastroesophageal reflux disease (GERD) patients who are refractory to acid-suppressive therapy. Stress affects visceral sensitivity and exacerbates heartburn in GERD. Peripheral CRH is a key mediator of the gut stress response. We hypothesize that CRH increases esophageal sensitivity and alters esophageal motility in health. Esophageal sensitivity to thermal, mechanical, electrical, and chemical stimuli was assessed in 14 healthy subjects after administration of plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 51 publications
1
15
0
1
Order By: Relevance
“…Clinical studies have found that CRH within the cerebrospinal fluid was positively correlated with pain perception in patients with chronic pain (McLean et al, 2006 ). A non-selective CRH antagonist decreased pain induced by colonic distension, while intravenous CRH induced esophageal hypersensitivity to distension in healthy volunteers, with no changes in perception of other noxious stimuli (Sagami et al, 2004 ; Broers et al, 2017 ). Intravenous CRH also increased abdominal pain and amygdala blood flow in both healthy volunteers and IBS patients (Tanaka et al, 2016 ).…”
Section: Neurotransmitters In Stress Pathways That Modulate Visceral mentioning
confidence: 99%
“…Clinical studies have found that CRH within the cerebrospinal fluid was positively correlated with pain perception in patients with chronic pain (McLean et al, 2006 ). A non-selective CRH antagonist decreased pain induced by colonic distension, while intravenous CRH induced esophageal hypersensitivity to distension in healthy volunteers, with no changes in perception of other noxious stimuli (Sagami et al, 2004 ; Broers et al, 2017 ). Intravenous CRH also increased abdominal pain and amygdala blood flow in both healthy volunteers and IBS patients (Tanaka et al, 2016 ).…”
Section: Neurotransmitters In Stress Pathways That Modulate Visceral mentioning
confidence: 99%
“…A recent study from Belgium demonstrated that intravenous CRH administration increased esophageal sensitivity to mechanical distention in healthy subjects. 11 Our study demonstrated that acute stress, simulated by intravenous CRH, significantly decreased the electrical threshold of esophageal perception. In addition, to the IPT, we also measured ACTH and cortisol levels to verify that subjects were exposed to a true stress load.…”
Section: Discussionmentioning
confidence: 50%
“…Subsequently, after deflating the balloon, the probe was retracted 10 cm proximal to the LES. More details on the multimodal stimulation test are described elsewhere, briefly; thermal (recirculating a heated solution through the balloon (5 mL NaCl 0.09%, 37‐62°C)), mechanical (balloon distention), electrical (2 stimulation electrodes proximal to the balloon give short electrical block pulses with duration of 1 ms at 200 Hz; maximum current was limited to 40 mA), and chemical sensitivity (0.1 N HCl solution for a maximum period of 30 minutes at 2 mL/min or until pain tolerance threshold is reached) were assessed by this protocol. The positioning and tolerance of the probe are comparable to those of classical esophageal manometry and balloon distention probes …”
Section: Methodsmentioning
confidence: 99%